The Role of Organic and Mineralogical Interaction Products in the Structure Forming and Humus Forming of the Basic Types of Soils in the Center of Russian Plain - Z. S. Artemyeva; N. P. Kirillova (Бюллетень Почвенного института им. В.В. Докучаева, 2017)
The modified variant of granulo-densimetric fractionating method allows us to separate the functionally valuable compounds of the soil organic matter (OM) with different localization within the soil matrix. It gives us an opportunity to specify their role in the soil forming processes, and also the factors, which regulate their forming and changes under the impact of the external conditions. The free (non-aggregated) OM, which is localized in space between aggregates, and stabilized OM in the composition of microaggregates. Such an approach allows us to assess the soil microstructure more validly. The two groups of microaggregates are separated in the soil. They are differed in the degree of sustainability to dispergating impact of ultrasound. There are also differences in the form, structure, composition and properties of organic and organo clayey compounds, and the type of stabilizing agents. The correlation between the microstructural organization and OM sustainability was set for the zonal range of basic soil types of Central Russia. It is revealed that the micro-agregation degree in the soil of the zonal range is increased due to the heaving of the soil texture, which reflects the dominating role of the organo-clayey particles in their forming. The difference between the sustainable and unsustainable microagregates is in the amount of these particles and in character of the organic compounds.